PEMBERIAN LOGO, STIKER, PROMOSI INSTRAGRAM DAN PEMBUATAN NIB (NOMOR INDUK USAHA) - Amilia Ratna Dewi; Bayu Teguh Wibowo; Akhmad Nurrofi; Nuruddin Mahmud (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
With the existence of home industries, national economic growth can increase through strengthening regional economies. The MSME partnering in this community service activity is a Snack Manufacturing MSME, located at Jalan Tambra Dalam 2 RT03/RW09 No. 9 Kuningan, North Semarang. Some of the problems faced by this MSME include product type management, namely a lack of innovation or product differentiation, and inadequate marketing. The activity method used to address the partners' problems is interviews and training conducted in the form of sharing. The goal of this activity is to provide an understanding of the importance of innovation and good business management to enable businesses to grow. The results of this community service activity include business permits, product innovation ideas and product differentiation, and logo and sticker creation.